The methodology of positive economics : reflections on the Milton Friedman legacy - Mäki, Uskali (Cambridge : Cambridge University Press, 2009)
Milton Friedman's 1953 essay 'The methodology of positive economics' remains the most cited, influential, and controversial piece of methodological writing in twentieth-century economics. Since its appearance, the essay has shaped the image of economics as a scientific discipline, both within and outside of the academy. At the same time, there has been an ongoing controversy over the proper interpretation and normative evaluation of the essay. Perceptions have been sharply divided, with some viewing economics as a scientific success thanks to its adherence to Friedman's principles, others taking it as a failure for the same reason. In this book, a team of world-renowned experts in the methodology of economics cast new light on Friedman's methodological arguments and practices from a variety of perspectives. It provides the 21st century reader with an invaluable assessment of the impact and contemporary significance of Friedman's seminal work.
The methodology of positive economics (1953) / Milton Friedman -- Reading the methodological essay in twentieth-century economics: map of multiple perspectives / Uskali Mäki -- Early drafts of Friedman's methodology essay / J. Daniel Hammond -- Unrealistic assumptions and unnecessary confusions: rereading and rewriting F53 as a realist statement / Uskali Mäki -- The influence of Friedman's methodological essay / Tom Mayer -- Did Milton Friedman's positive methodology license the formalist revolution? / D. Wade Hands -- Appraisal of evidence in economic methodology / Melvin W. Reder -- The politics of positivism: disinterested predictions from interested agents / David Teira Serrano and Jesús Zamora Bonilla -- Friedman's 1953 essay and the marginalist controversy / Roger E. Backhouse -- Friedman (1953) and the theory of the firm / Oliver E. Williamson -- Friedman's selection argument revisited / Jack Vromen -- Expected utility and Friedman's risky methodology / Chris Starmer -- Milton Friedman's stance: the methodology of causal realism / Kevin D. Hoover -- On the right side for the wrong reason: Friedman on the Marshall-Walras divide / Michel De Vroey -- The debate over F53 after fifty years / Mark Blaug -- Final word / Milton Friedman.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Friedman, Milton, -- 1912-2006.; Free enterprise